Implementasi Black Box Testing pada Aplikasi Sistem Kasir dengan Menggunakan Teknik Equivalence Partitions - Huda, Muhammad Nurul; Burhan, Muhammad; Satibi, Ahmad; Pradita, Helmy Agus; Saifudin, Aries; Kusyadi, Irpan (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
Testing an application serves to check whether an application / program is running with what is desired or whether there are still errors / errors that need to be corrected so that the program created into a quality program. Software testing method consists of two types, namely Blackbox testing and Whitebox Testing where many are used in the time of the testers to check the program is appropriate or not with what they want. Testing this time the software that will be tested using the Blackbox testing method, this time testing only has the purpose to check the program being tested whether it is in accordance with the benefits that the manufacturer wants to the program without the tester having to know what program code is used in the application. Testing the Blackbox method is really a variety of one is Equivalence Partitions. which is utilized by us in the testing process this time. This technique is a trial in which the tester inputs data on all pages in the cashier application process, each page in the form of input will be tested and classified based on its function whether it is valid or not. What is desired in this test is the creation of the quality of the software produced in accordance with the benefits expected by the creator, and can also provide benefits to buyers who will use it.